If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + -12 = 5 Reorder the terms: -12 + 6z = 5 Solving -12 + 6z = 5 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6z = 5 + 12 Combine like terms: -12 + 12 = 0 0 + 6z = 5 + 12 6z = 5 + 12 Combine like terms: 5 + 12 = 17 6z = 17 Divide each side by '6'. z = 2.833333333 Simplifying z = 2.833333333
| 10x-22+5x=3 | | (78).425= | | 5x=3x^2 | | (5x+3)*(24-3x)=0 | | x^2+21x+32=12 | | 8x-8=x+7 | | b=(11b+14)(8-10b) | | 5x+8=3(x+4) | | b=8a(8A-13) | | 8p+p^2=105 | | 8x+19=2x+163 | | b=-(-5a-3)+(-5+8a) | | -3p+2q-3r= | | 3x-7=2x+18 | | 253-3x=42x+23 | | 11a+6b+24ao+18b= | | 125=5x^3 | | 4x^3+9x^2-2=0 | | (h*h)+h=6 | | 4Y-3=29 | | 2(h*h)+h=21 | | 6(h*h)+2h=28 | | 0=x^2-78x-1911 | | 2Y=128 | | Y-7=21 | | 5y+11=3(y+7) | | X+16=35 | | 7x+5=(2x+3)(4x+1) | | 2x^2+14x+54=0 | | x^2+14+54=0 | | 7x-x^2-15=0 | | 10(3k+1)=2(9+11) |